1968
DOI: 10.1042/bj1080561
|View full text |Cite
|
Sign up to set email alerts
|

The stereospecificity of α-chymotrypsin

Abstract: 1. The rates of deacylation of acyl-alpha-chymotrypsins in which the hydrogen-bonding capacity of the acylamino group of the substrate has been systematically removed were measured. 2. The ratio of deacylation rates of l- and d-acyl-enzymes is found to depend largely on the existence in the substrate of an amido -NH- group. 3. The data presented agree with the postulate that the stereospecificity of alpha-chymotrypsin is exercised in catalytic rather than binding steps, and that the active site of the enzyme p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

1970
1970
1995
1995

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(44 citation statements)
references
References 31 publications
1
43
0
Order By: Relevance
“…This suggests that the specificity and reactivity determinants of a macromolecule are derived from its architecture and structural organization. Some of the studies which have used the three-dimensional structural data to exam ine the serine proteases include modeling the process of zymogen activation [20], describ ing the specificity determinants of the active site [23,27] and most recently, prediction of the structure of homologous enzymes by structure extension [22], observation of an activation domain [25], and selection of and testing the effects of site-directed mutagene sis on active site residues of trypsin [16]. Other studies focused on the observation of protein folding domains in all members of this enzyme family [4,37], comparison of serine proteases from prokaryotic and eukaryotic sources [18], comparison with evolutionarily related but nonhomologous serine proteases (e.g., subtilisin [17]), and examination of both protein and inhibitor surface areas buried during formation of macromolecular complexes [14], Although the studies listed above have probed many aspects of the role of structure in defining the…”
mentioning
confidence: 99%
“…This suggests that the specificity and reactivity determinants of a macromolecule are derived from its architecture and structural organization. Some of the studies which have used the three-dimensional structural data to exam ine the serine proteases include modeling the process of zymogen activation [20], describ ing the specificity determinants of the active site [23,27] and most recently, prediction of the structure of homologous enzymes by structure extension [22], observation of an activation domain [25], and selection of and testing the effects of site-directed mutagene sis on active site residues of trypsin [16]. Other studies focused on the observation of protein folding domains in all members of this enzyme family [4,37], comparison of serine proteases from prokaryotic and eukaryotic sources [18], comparison with evolutionarily related but nonhomologous serine proteases (e.g., subtilisin [17]), and examination of both protein and inhibitor surface areas buried during formation of macromolecular complexes [14], Although the studies listed above have probed many aspects of the role of structure in defining the…”
mentioning
confidence: 99%
“…Kinetic measurements were similar to those described previously 12-41. The k3 (ms) value, equal to kcat, for nitrophenyl esters [6,7] , Was determined under conditions of stationary cuchymotryptic hydrolysis of rrans-NPNC, with [S10 9 Km(app) (where Km (aPPJ < lo-' M). The rate of pnitrophenolate ion liberation was followed spectrophotometrically (400 nm)at [S],, = 1.7 X lo-' M; [El0 was varied from 7X 10-8Mto2X lo-'M.…”
Section: Methodsmentioning
confidence: 99%
“…(1966) and Ingles and Knowles (1968) have clearly demonstrated that the presence of an aromatic side chain and an acyl amino group on the a-carbon of L-acylenzymes are essential for rapid deacylation. More recent chemical and crystallographic evidence on the hydrolysis of oligopeptide substrates and inhibition with peptide chloromethyl ketones has delineated an extended peptide binding site for the substrate in chymotrypsin (D. Segal, personal communication) and (Segal et al, 1971).…”
Section: Lyzed Its Amino Acid Composition Is Listed Inmentioning
confidence: 99%